Majorana stellar representation of twisted photons - Nicolas Fabre; Andrei B. Klimov; Romain Murenzi; Jean-Pierre Gazeau; Luis L. Sánchez-Soto (Physical Review Research, 2023)
Majorana stellar representation, which visualizes a quantum spin as points on the Bloch sphere, allows quantum mechanics to accommodate the concept of trajectory, the hallmark of classical physics. We extend this notion to the discrete cylinder, which is the phase space of the canonical pair angle and orbital angular momentum. We demonstrate that the geometrical properties of the ensuing constellations aptly encapsulate the quantumness of the state.